A Shelter-associated Tuberculosis Outbreak: A Novel Strain Introduced Through Foreign-born Populations - Moreau, Danusia (Can J Public Health, 2012)
Objective: An outbreak of tuberculosis (TB) in a large urban apartment building and three homeless shelters within a one-block radius in Edmonton, Alberta occurred between 2008 and 2009. The purpose of this report is to describe the transmission dynamics of this multiethnic, multicentre inner-city TB outbreak. Methods: A retrospective chart review was conducted through the Integrated Public Health Information Systems (iPHIS) to extract demographic, clinical and treatment data as well as data for contacts for all 19 cases involved in the outbreak. TB isolates were genotyped using molecular IS6110 restriction fragment-length polymorphism (RFLP). Categorical variables were compared using Fisher’s exact test and continuous variables were analyzed using the Kruskal Wallis test. Results: Two groups were identified through genotyping. One group consisted of 9 cases with a newly identified TB genotype circulating in Alberta. All of the cases in this group were among males and two thirds were among individuals from northeast Africa, with subsequent transmission into Canadian-born populations through exposure during shelter stays. The second group (n=3) identified were infected by a previously circulating strain of TB in Alberta and consisted of Canadian-born Aboriginal people. Conclusion: This study demonstrates the transmission of a novel TB strain from foreign-born populations to Canadian-born populations through location-based settings serving vulnerable populations. This study highlights the changing demographic and emerging health concerns for under-housed populations in Canada.